Otologic and Audiology Concerns of Microtia Repair - Ali, Kausar; Mohan, Kriti; Liu, Yi-Chun (Seminars in Plastic Surgery, 2017)
Microtia is a congenital auricular deformity that commonly presents with associated congenital aural atresia. The most acute concern in these patients is concomitant hearing loss at birth. A team-based approach by plastic surgeons and otologists is necessary to address both the otologic and audiologic concerns of microtia and atresia. Hearing rehabilitation is imperative; yet it should not compromise the aesthetic components of reconstruction and vice versa. Here, the authors propose a framework to evaluate and manage patients with microtia and atresia with the goal of optimizing functional and cosmetic outcomes.
Keywords: microtia; aural atresia; ear reconstruction; atresiaplasty; hearing rehabilitation